The influence of cadence on fatigue during maximal sprint cycling in world-class and elite sprint cyclists - Wackwitz, T.; Minahan, C.; Menaspà, P.; Crampton, M.; Bellinger, P. (Journal of Sports Sciences, 2023)
Optimising cadence through appropriate gear selection is a key consideration for track sprint cycling performance, yet the influence of cadence on fatigue (i.e., decrement in power output) within a maximal sprint is not well understood. The aim of this study was to identify the influence of cadence on fatigue during maximal sprint cycling. Eleven world-class and elite track sprint cyclists (n = 6 men, maximal power output (Pmax) = 1894 ± 351 W, optimal cadence (Fopt) = 134 ± 8 rev·min-1: n = 5 women, Pmax = 1114 ± 80 W, Fopt = 124 ± 8 rev·min-1) completed two testing sessions where power-cadence profiles were constructed to determine the Fopt associated with Pmax. Cyclists also performed three maximal 15-s sprints (Fopt, ±15%Fopt) to identify fatigue per pedal stroke across these cadence ranges. There was no significant difference (p = 0.2) in the absolute fatigue per pedal stroke when cadence was fixed 15% above (16.7 ± 6.1 W·stroke-1) and below (15.3 ± 5.1 W·stroke-1) Fopt. Similarly, there was no significant difference in the relative fatigue per pedal stroke (% peak power·stroke-1) across Fopt and ± 15%Fopt trials (p = 0.12). The relative decrement in power output is equivalent across the ± 15%Fopt cadence range. As such, a higher-geared, lower-cadence approach to maximal sprint cycling could be a viable method to minimise maximal pedal strokes and reduce the decrement in power output.